Ensuring Labor Rights in the Age of AI: Strengthening Corporate Social Responsibility and Human Security in Vietnam - Nguyen, Trung (UIN Sunan Gunung Djati, 2025)
This study examines Corporate Social Responsibility (CSR) as a legal mechanism to protect the right to work in Vietnam amid disruptions caused by Artificial Intelligence (AI). While AI enhances productivity, it threatens labor rights and human security, particularly in labor-intensive industries. The research critically evaluates Vietnam’s legal framework, including the 2013 Constitution (Article 35), the 2020 Labor Code, and the 2020 Enterprise Law, in alignment with international human rights standards such as the ICESCR, ICCPR, and ILO conventions. Drawing from global best practices, Germany’s Digital Pact for Labor and Japan’s Society 5.0 demonstrate how legal frameworks can balance AI-driven economic transformation with labor protection and human security. Sweden’s CSR model ensures corporate accountability through mandatory reporting and supply chain oversight, while Singapore’s Skills Future initiative offers government-funded reskilling to support workforce adaptation. This study proposes legally binding CSR obligations, fiscal incentives for sustainable employment, enhanced regulatory oversight, and a National Workforce Retraining Fund to align Vietnam’s policies with international labor standards. By embedding CSR into law, Vietnam can balance economic growth with labor protection and human security, ensuring a just and sustainable transition in the AI era.